PERAN PEMERINTAH DESA DAN PARTISIPASI MASYARAKAT DALAM PEMBINAAN MORAL PARA REMAJA DI DESA KARANGTENGAH KECAMATAN WINONGAN KABUPATEN PASURUAN - Muhammad Dwiki Ilhamsyah; Ahmad Subekti; Indhra Mustofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The formation of noble morals is the main goal in Islamic religious education. In addition, Islamic religious education also aims to form a Muslim personality with a pattern of piety, namely by realizing a good personality to the fullest in order to obtain the perfection of life. This study aims to describe the moral portrait of adolescents in Karangtengah Village, Winongan District, Pasuruan Regency, to describe the role of the village government in fostering youth morale in Karangtengah Village, Winongan District, Pasuruan Regency and to describe community participation in youth moral development in Karangtengah Village, Winongan District, Pasuruan Regency. Researchers used data analysis techniques according to Miles and Huberman. Checking the validity of the data used is a test of credibility, transferability, dependability, confirmabilit. The results of this study indicate that the portrait of teenagers in Karangtengah Village has undergone many changes in all respects. Starting from the mindset, in terms of education, teenagers who are more advanced.